ACs5Bi4(PO4)2(P2O7)3 (A = K, Rb and Cs) with two kinds of isolated P–O groups designed by dimensional reduction theory. Issue 24 (4th November 2021) - Liu, Shiwei; Chen, Jiale; Wu, Hongping; Yu, Hongwei; Hu, Zhanggui; Wang, Jiyang; Wu, Yicheng
Abstract : ACs5 Bi4 (PO4 )2 (P2 O7 )3 (A = K, Rb and Cs) were successfully designed and synthesized by dimensional reduction theory with a system of A2 O–Bi2 O3 –P2 O5 . Abstract : The dimensional reduction theory is applied to an A2 O–P2 O5 –Bi2 O3 system where P2 O5 serves as a binary parent while A2 O and Bi2 O3 are regarded as dimensional reduction agents. Thus, three novel phosphates ACs5 Bi4 (PO4 )2 (P2 O7 )3 (A = K, Rb and Cs) have been prepared through the high-temperature solution method. Single-crystal X-ray diffraction measurements reveal that they all crystallize in the monoclinic space group P 21 / c (no. 14) and in their structures, two different kinds of P–O units, i.e. isolated PO4 tetrahedra and P2 O7 dimers, are interconnected by Bi–O groups to construct a 3 ∞ [Bi4 (PO4 )2 (P2 O7 )3 6− ] framework. Note that with the change of cationic size in their structures, the Bi 3+ cations also exhibit flexible coordination, i.e. BiO5 and BiO6 polyhedra in KCs5 Bi4 (PO4 )2 (P2 O7 )3 and only BiO6 polyhedra in Cs6 Bi4 (PO4 )2 (P2 O7 )3, suggesting that combining the flexible coordination of Bi 3+ cations with phosphates based on dimensional reduction theory is an effective strategy to guide the synthesis of new compounds.